Medical Language Pathology - Lain Entralgo, Pedro (1957)
They taught Hippocrates and Galen, in principle, all that is food is not poison. "What does not kill, fattens", they say our people, tougher and radically. This seems to be the norm chaired the growth of a language. But, by God, seek to physicians fattening our language is comparable to that engendered mild hip Venus Callipyge, not the buttocks produced as monstrous as the Hottentot Venus. For this purpose, the dietician, aesthetic and linguistic turn, I have sketched above observations dwindling .